Mission and Low Vision: A Visually Impaired Museologist's Perspective on Inclusivity - Wapner, Joseph (Disability Studies Quarterly, 2013)
The author gives a detailed account of a visit to the Seattle Art museum, with observations about audio tours, staff training, signage, audio backgrounds to visual displays, and other exhibit elements. He argues that inclusive design will only come about when underserved groups are understood “not as targets to be reached but rather as the knowledgeable curators of their own experiences.” Key words: blindness, low vision, museum, inclusive design, museum access, accessibility, Seattle Art Museum